Structure-based virtual screening identifies a small-molecule inhibitor of the profilin 1–actin interaction - Gau, David (J Biol Chem, 2018)
Profilin 1 (Pfn1) is an important regulator of the actin cytoskeleton and plays a vital role in many actin-based cellular processes. Therefore, identification of a small-molecule intervention strategy targeted against the Pfn1–actin interaction could have broad utility in cytoskeletal research and further our understanding of the role of Pfn1 in actin-mediated biological processes. Based on an already resolved Pfn1–actin complex crystal structure, we performed structure-based virtual screening of small-molecule libraries to seek inhibitors of the Pfn1–actin interaction. We identified compounds that match the pharmacophore of the key actin residues of Pfn1–actin interaction and therefore have the potential to act as competitive inhibitors of this interaction. Subsequent biochemical assays identified two candidate compounds with nearly identical structures that can mitigate the effect of Pfn1 on actin polymerization in vitro. As a further proof-of-concept test for cellular effects of these compounds, we performed proximity ligation assays in endothelial cells (ECs) to demonstrate compound-induced inhibition of Pfn1–actin interaction. Consistent with the important role of Pfn1 in regulating actin polymerization and various fundamental actin-based cellular activities (migration and proliferation), treatment of these compounds reduced the overall level of cellular filamentous (F) actin, slowed EC migration and proliferation, and inhibited the angiogenic ability of ECs both in vitro and ex vivo. In summary, this study provides the first proof of principle of small-molecule–mediated interference with the Pfn1–actin interaction. Our findings may have potential general utility for perturbing actin-mediated cellular activities and biological processes.